If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15g + -20 = -25 Reorder the terms: -20 + 15g = -25 Solving -20 + 15g = -25 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '20' to each side of the equation. -20 + 20 + 15g = -25 + 20 Combine like terms: -20 + 20 = 0 0 + 15g = -25 + 20 15g = -25 + 20 Combine like terms: -25 + 20 = -5 15g = -5 Divide each side by '15'. g = -0.3333333333 Simplifying g = -0.3333333333
| (.3r+.3)(r+.7)= | | ln(x)+ln(1+2u)=ln(a) | | 1.3x+3(x+8.2)=37.5 | | 4b+15=-27 | | 3x+5+2=2 | | 12t+4=100 | | 11x=12a-21 | | b/8=50/20 | | x^2+13=-22 | | 11a=12-21 | | 40+1x=26+3x | | -2x(2+3x)4=24 | | 28x-5=22+15x | | 4a+a-11=24 | | 10/15=m/39 | | 778+200= | | -9a=-12-45 | | -9a=-12-45 | | 6y+2=5y-3+y | | y/6=15/9 | | (0.9r-4)(1.2r+3)= | | 7x-29-21x=3-12+2x | | F-1.5=3.5 | | 14/8=y/20 | | 6(3.625)+5y=33 | | 10g-14=-72g+50 | | 6y+5=6y-9 | | 3y^3(3y+4)(y-5)= | | 3m-6=4m+7-m | | 9m-12=2m+8 | | (v-5)(v+7)= | | 6x+5(2x-5)=33 |